Expectant versus surgical management of incomplete abortions caused by self-intake of abortifacient drugs: results from a randomized controlled trial - Singh, Ankita; Kushwah, Devendra Singh; Khatik, Neha; Kushwah, Beenu (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Termination of unwanted pregnancies with medical method using recommended protocol based abortifacient drugs is a standard practice followed by obstetricians and gynaecologists worldwide which has a very successful outcome. However, self-administration of these drugs has become rampant because of certain social and practical issues resulting in complications and incomplete abortions as when these drugs are self-administered, recommended protocol is not generally followed. Traditionally incomplete abortions are managed by surgical curettage which itself is associated with procedure related complication and has been challenged by recent studies. Based on these studies many international guidelines have come out in support of expectant management of incomplete abortions. This study compared both of these management protocols to treat incomplete abortions caused by unprescribed intake of abortifacient drugs. Methods: This was a one-year long prospective randomized controlled study in which total 782 females were randomized into two groups of 371 and 411. Group 1 was offered expectant management while group 2 was offered surgical curettage. Results were analysed using appropriate statistical tests. Results: Group 1 showed a success rate of 86% while group 2 showed a success rate of 90% which was comparable. Overall complication rate was found to be higher in Surgical curettage group than in the group which underwent expectant management group. Conclusions: Considering a very high number of patients coming with incomplete abortions caused by self-medication in present practice, expectant management seems to be a safer and more effective method and should be practice more widely.